Leveraging the Incoporation of Youtube and Whatsapp to Support Students Understanding and Learning Motivation in Senior High School - Tjokorda Istri Oktadiana Dewi; Putu Adi Krisna Juniarta (Journal of Psychology and Instruction, 2023)
The use of social media in higher education provided a collaborative learning environment and increased peer engagement and interaction between educators and students. Nowadays, many students used social media in their daily lives to easily communicate over long distances without having to meet directly at school. Social media was important for students because it served as a place for gathering and searching for information. Therefore, the integration of social media into learning process can be an innovation for today’s learning strategy. This research was conducted to investigate students' perceptions of their learning motivation towards the implementation of social media-based online learning at SMAN 1 Ubud. Some data collection techniques used for collecting different types of data, such as field research, participant observation, and in-depth interviews, as proposed by Bungin (2010). The qualitative approach was employed to analyze the data by using the thematic analysis model proposed by Braun and Clarke (2006). The process of thematic analysis involved analyzing the data, where each question contributed to the understanding of the research problem and led to a holistic view of the overall picture. The result of this research shows that social media can assist students in developing their cognitive aspects. The students' learning motivation increases due to several factors within social media, such as diverse content, various learning sources, and the presence of animations, visuals, and audio. These positive impacts make students enthusiastic about learning and interested in classroom activities. Ultimately, these factors also have an impact on their cognitive development.